Clinical characteristics of enterovirus A71 neurological disease during an outbreak in children in Colorado, USA, in 2018: an observational cohort study. Issue 2 (February 2020) - Messacar, Kevin; Spence-Davizon, Emily; Osborne, Christina; Press, Craig; Schreiner, Teri L; Martin, Jan; Messer, Ricka; Maloney, John; Burakoff, Alexis; Barnes, Meghan; Rogers, Shannon; Lopez, Adriana S; et al.
Summary: Background: In May, 2018, Children's Hospital Colorado noted an outbreak of enterovirus A71 (EV-A71) neurological disease. We aimed to characterise the clinical features of EV-A71 neurological disease during this outbreak. Methods: In this retrospective observational cohort study, children (younger than 18 years) who presented to Children's Hospital Colorado (Aurora, CO, USA) between March 1 and November 30, 2018, with neurological disease (defined by non-mutually exclusive criteria, including meningitis, encephalitis, acute flaccid myelitis, and seizures) and enterovirus detected from any biological specimen were eligible for study inclusion. The clinical characteristics of children with neurological disease associated with EV-A71 were compared with those of children with neurological disease associated with other enteroviruses during the same period. To explore the differences in clinical presentation of acute flaccid myelitis, we also used a subgroup analysis to compare clinical findings in children with EV-A71-associated acute flaccid myelitis during the study period with these findings in those with enterovirus D68 (EV-D68)-associated acute flaccid myelitis at the same hospital between 2013 and 2018. Findings: Between March 10 and Nov 10, 2018, 74 children presenting to Children's Hospital Colorado were found to have enterovirus neurological disease; EV-A71 was identified in 43 (58%) of these children. The median age of the children with EV-A71 neurological disease was 22·7 months (IQR 4·0–31·9), and most of these children were male (34 [79%] children). 40 (93%) children with EV-A71 neurological disease had findings suggestive of meningitis, 31 (72%) children showed evidence of encephalitis, and ten (23%) children met our case definition of acute flaccid myelitis. All children with EV-A71 disease had fever and 18 (42%) children had hand, foot, or mouth lesions at or before neurological onset. Children with EV-A71 disease were best differentiated from those with other enteroviruses (n=31) by the neurological findings of myoclonus, ataxia, weakness, and autonomic instability. Of the specimens collected from children with EV-A71, this enterovirus was detected in 94% of rectal, 79% of oropharyngeal, 56% of nasopharyngeal, and 20% of cerebrospinal fluid specimens. 39 (93%) of 42 children with EV-A71 neurological disease who could be followed up showed complete recovery by 1–2 months. Compared with children with EV-D68-associated acute flaccid myelitis, children with EV-A71-associated acute flaccid myelitis were younger, showed neurological onset earlier after prodromal symptom onset, had milder weakness, showed more rapid improvement, and were more likely to completely recover. Interpretation: This outbreak of EV-A71 neurological disease, the largest reported in the Americas, was characterised by fever, myoclonus, ataxia, weakness, autonomic instability, and full recovery in most patients. Because EV-A71 epidemiology outside of Asia remains difficult to predict, identification of future outbreaks will be aided by prompt recognition of these distinct clinical findings, testing of non-sterile and sterile site specimens, and enhanced enterovirus surveillance. Funding: None.